2016
DOI: 10.1111/ajr.12307
|View full text |Cite
|
Sign up to set email alerts
|

Client perspectives on an Aboriginal community led oral health service in rural Australia

Abstract: The implementation of a new community led oral health service to Northern NSW Aboriginal communities was shown here to be well-utilised, respected and in an area of high need. The collaborative approach could be continued to be utilised to implement targeted, community led health promotion programs to facilitate and encourage better oral health practices for the Aboriginal children in these communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…25 Extensive cultural competence training provided prior to relocation, gave them some cultural awareness but they reported it was the immersion into the culture through living and working in the community and being open to learning from the community members, that increased their ability to be culturally competent. A survey of children and their parents who used the service during 2014 showed that they felt valued and respected when receiving care, 26 indicating that this learned cultural competence had translated into helping to build a culturally competent health service.…”
Section: Discussionmentioning
confidence: 99%
“…25 Extensive cultural competence training provided prior to relocation, gave them some cultural awareness but they reported it was the immersion into the culture through living and working in the community and being open to learning from the community members, that increased their ability to be culturally competent. A survey of children and their parents who used the service during 2014 showed that they felt valued and respected when receiving care, 26 indicating that this learned cultural competence had translated into helping to build a culturally competent health service.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies with Australian Aboriginal communities revealed that the effectiveness of a health program is linked to how well the program adopts the community's cultural practices, knowledge, and involves community members to participate and lead the program. [50][51][52][53] These factors highlight the importance of the community to be directly involved with the development of the training program. In the context of the broader PAR program of research, the team will need to build the training program integrating the participants' suggested content and delivery, using the insights gained through these focus groups.…”
Section: Discussionmentioning
confidence: 99%
“…Two published studies by Irving et al report positively on the experience of the service from the community perspective (Irving et al, 2016a) and the clinicians living in the communities (Irving et al, 2016b). In addition, a paper comparing this model of oral health care with a visiting service model over two years (2014 and 2015) found that this service model delivered 47% more treatment at 25.2% of the cost of a visiting service .…”
Section: Shared Aspects Of Controlmentioning
confidence: 99%